2021
DOI: 10.1109/access.2021.3114646
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Greedy Hybrid Bio-Inspired Routing Protocol to Improve IoV

Abstract: New vehicles are now expected to be involved in the rapid development of Intelligent Transport Systems (ITS). Vehicular Ad hoc NETwork (VANET) is the basic equipment used for the production of ITSs with a rapid and dynamic network topology. The increasing number of connected vehicles and the need for real-time data processing has created a growing demand for turning real VANETs into an automotive Internet of Vehicle (IoV) for achieving a goal of an effective and smart future transportation system. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The simulation results also shows that the AGHBI works well with both V2V and V2I environments. It significantly impacts PDR and delays while maintaining minimum hop count across all vehicles [63]. 15 Wireless Communications and Mobile Computing decrease the packet delay.…”
Section: Opportunistic and Position-based Routing (Opbr)mentioning
confidence: 99%
“…The simulation results also shows that the AGHBI works well with both V2V and V2I environments. It significantly impacts PDR and delays while maintaining minimum hop count across all vehicles [63]. 15 Wireless Communications and Mobile Computing decrease the packet delay.…”
Section: Opportunistic and Position-based Routing (Opbr)mentioning
confidence: 99%
“…MADCR protocol's performance is compared to that of comprehensive learning particle swarm optimization, ant colony optimization, and clustering algorithm for IoV based on dragonfly optimizer. It is observed that the suggested MADCR methodology boosts PDR by 6-16% while decreasing latency by 6-100 ms in real-time scenarios (Sennan et al, 2021) In (Attia et al, 2021), authors proposed an advanced greedy hybrid bio-inspired (AGHBI) routing algorithm based on the greedy forwarding system, a modified hybrid routing scheme using an artificial bee colony (ABC) optimization, that helps choose a route with the highest QoS parameters and maintains a path with the least amount of overflow. AGHBI uses two steps: a greedy scheme to transfer the packets is used to the nearest destination, followed by a modified hybrid routing system that uses an ABC optimization algorithm for a significant QoS route and preserves the route information with the least amount of overflow.…”
Section: Related Workmentioning
confidence: 99%
“…In (Attia et al , 2021), authors proposed an advanced greedy hybrid bio-inspired (AGHBI) routing algorithm based on the greedy forwarding system, a modified hybrid routing scheme using an artificial bee colony (ABC) optimization, that helps choose a route with the highest QoS parameters and maintains a path with the least amount of overflow. AGHBI uses two steps: a greedy scheme to transfer the packets is used to the nearest destination, followed by a modified hybrid routing system that uses an ABC optimization algorithm for a significant QoS route and preserves the route information with the least amount of overflow.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This method showed less cost, jitter, and delay compared to other methods. To improve the performance of IoV, a bioinspired advanced greedy hybrid routing protocol was proposed in [58], where a bee colony optimization combined with a greedy algorithm is used to choose the best route with high service quality and select a route with the minimum overflow. The simulation outcomes show that this protocol works well in both V2I and V2V environments and has a significant impact on enhancing delay and packet delivery ratio while maintaining a minimum hop count across all vehicles and reasonable overhead.…”
Section: Performance Of Swarm Intelligence-based Bioinspiredmentioning
confidence: 99%